Role of Endogenous and Induced Regulatory T Cells During Infections - Wohlfert, Elizabeth (2008)
BACKGROUND: Various populations of regulatory cells, including Foxp3+ T(Reg), have been shown to play a central role in the maintenance of peripheral homeostasis and establishment of controlled immune responses. OBJECTIVE: In this review, we discuss current hypotheses and points of polemic associated with the origin, mode of action, and antigen specificity of both endogenous and induced regulatory T cells during infections.